Analisis Sektor Basis Dalam Peningkatan Pertumbuhan Ekonomi Di Kabupaten Padang Lawas Utara - Muhammad Rizky Siregar; Muhammad Arif; Juliana Nasution (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
Economic development must focus on the base sector by maximizing existing resources in the regions in order to increase economic growth as seen from the development of the Gross Regional Domestic Product (GRDP). Based on the summary above, the purpose of this research is to maximize the utilization of existing resources in the North Padang Lawas Regency area with the priority to find out how the base sector is utilized and how changes in economic structure can increase regional economic growth in North Padang Lawas Regency by making comparisons with provincial economic conditions a very important reference area to study in depth. This type of research is descriptive qualitative research using secondary and primary data. This study uses 3 analytical tools namely Location Quotien Analysis, Klassen Typology Analysis, and Growth Ratio Model. To which the results of this analysis will be responded to or given statements by related sources to reinforce the results of the analysis. According to the research results, there are 4 (four) sectors which are the base sectors namely; Agriculture, forestry and fishery sectors; Electricity and gas procurement sector; Construction sector; as well as government administration, defense and mandatory social security sectors. Where the base sector here plays an important role in the development of increasing economic growth in North Padang Lawas Regency, because people's income and business fields in this area mostly come from the base sector itself. The base sector is also always present and is a sector that has a positive value in various analytical tools used in this study.